2017
DOI: 10.1002/adma.201700530
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Low‐Symmetry Phases and Large Property Enhancements in Ferroelectric KNbO3 Bulk Crystals

Abstract: The design of new or enhanced functionality in materials is traditionally viewed as requiring the discovery of new chemical compositions through synthesis. Large property enhancements may however also be hidden within already well-known materials, when their structural symmetry is deviated from equilibrium through a small local strain or field. Here, the discovery of enhanced material properties associated with a new metastable phase of monoclinic symmetry within bulk KNbO is reported. This phase is found to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…A phase‐field model taking into account the polarization dynamics was used to simulate the domain and DW response in the BFO thin films under an ac electric field . The 2D simulation that was performed had 512 grids in the x ‐direction and 64 grids in the z ‐direction, with each grid representing 0.4 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase‐field model taking into account the polarization dynamics was used to simulate the domain and DW response in the BFO thin films under an ac electric field . The 2D simulation that was performed had 512 grids in the x ‐direction and 64 grids in the z ‐direction, with each grid representing 0.4 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The GHz response of ferroelectric DWs has been spatially resolved by microwave impedance microscopy (MIM) . For weakly charged walls in KNbO 3 crystals and transiently formed charged walls in lead zirconate (PZT) thin films, it was shown that the DW ac conductivity is dominated by the charge carriers, that is, σ ac ≈ σ dc = σ 2 ac . In contrast, the MIM result on hexagonal manganites (h‐ R MnO 3 ) and ferrites (h‐ R FeO 3 ) depends strongly on the DW orientation.…”
mentioning
confidence: 99%
“…In this contribution, K-doped AgNbO 3 (AN) is selected to investigate as the AN holding matrix exhibits antiferroelectricity and a large, high-E-field-induced polarization (P ~ 52C/cm 2 ) (15)(16)(17)(18). KNbO 3 , on the other hand, exhibits an FE phase (19) but can form binary (Ag 1−x K x )NbO 3 (AKN) solid solutions with AN (20). Within these AKN solid solutions, the relative stability of the FE and AFE phase can be modulated through tailoring of the composition to give a material with a high potential to realize a pressure-induced FE-AFE phase transition and potentially be able to serve as an effective alternative to lead-containing materials for energy harvesting and conversion applications.…”
Section: Introductionmentioning
confidence: 99%
“…The GHz DW conductivity has been recently studied by scanning microwave impedance microscopy (MIM) in several ferroelectrics [17][18][19] . In particular, charge-neutral DWs on the (001) surface of h-RMnO3, which show vanishingly small electrical conduction at dc 5 , exhibit very large ac conductivity at radio frequencies due to the collective DW vibration around its equilibrium position 19 .…”
mentioning
confidence: 99%